Determinants of Entrepreneurial Mindset in Education: Technology and Economic Constraints among 21st Century Teachers - ADEYEMO, Peter Oluwasola; CHUKWUEMEKA, Emeka Joshua; POPOOLA, Folakemi Mary (Ilorin Journal of Education, 2025)
Edupreneurship is transforming the educational landscape with innovative methods to tackle present demands. Implementing these novel approaches effectively rectifies the limitations of conventional teaching methods. This study investigates the factors affecting the development of an entrepreneurial mindset in the context of education, particularly by analyzing the impact of technological advances and economic constraints on methods of teaching in the 21st century. The study employed a qualitative method of inquiry, including semi-structured interviews with educators and edupreneurs from colleges of education, universities, and public secondary schools in Gwagwalada, Federal Capital Territory (FCT) of Nigeria. This offers a comprehensive understanding of how educators incorporate technological tools to tackle economic difficulties and foster entrepreneurial mindsets in their institutions. The specific attention given to Gwagwalada, FCT, provides a distinct viewpoint on the socio-economic and technological aspects that impact edupreneurship in a developing country. By conducting a comprehensive interview, data was collected that revealed key elements that influence the formation of an entrepreneurial mindset in the education domain. These factors include the availability of digital resources, support from educational institutions, and the ability to innovate even in the face of economic limitations. The results indicate that technology plays a significant role in encouraging edupreneurship, it is thus necessary to tackle economic obstacles and fully utilize technological capabilities. This study makes significant contributions to the current reservoir of knowledge on edupreneurship and gives vital insights for educators, policymakers, and entrepreneurs who are interested in leveraging technology to bring about educational transformation.